Coadsorption of ZnTPP and 2HMCTPP on Rutile TiO2(110) - Muth, Maximilian; Wolfram, Alexander; Steinrück, Hans-Peter; Lytken, Ole (ChemPhysChem, 2024)
Pure zinc tetraphenylporphyrin (ZnTPP) adsorbs on rutile TiO2(110) as flat-lying molecules, mostly interacting with the surface through weak van-der-Waals interactions. Pure monocarboxyphenyl triphenylporphyrin (2HMCTPP) forms a covalent bond to the rutile TiO2(110) surface through the carboxylic acid group, yielding densely-packed layers of upright-standing molecules. If given the chance, 2HMCTPP could therefore be expected to displace the weaker-bonding ZnTPP molecules. However, if 2HMCTPP is deposited on top of a ZnTPP layer, a coadsorption structure instead forms, with the carboxylic-acid groups of the 2HCMTPP molecules bonding to titanium atoms of the surface exposed by gaps between the molecules in the flat-lying ZnTPP adsorption structure.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Coadsorption; Oxides; Porpyhrins; XPS